(3OgfI GdTjN YHO Gddg GdOdGhj GdaGSjs - (3GdOdGhj GdaGSj, YHO Gddgs
(3ChdgG (B:s
(3UaI OgfI NGQbI hgj ef GdeLQHGJ hgj OgfI GdMceGA GdeJbOejf hgh Cf JCNP QWd eUQj Ch GcKQ ef GdQWd Hbdjd ef HQGOI GdeQjN GdNGdUI hGZSdgG LjOG HGdeGA s
(3BNQgG (B:s
(3hgcPG jchf Yedc cd eKbGd ef Jdc GdJQHI Ydi QWd GSQH hGdQWd Ydi CQHYI CQWGd CSQH McejI aGage Pdc hGdSdGe JeJ HYhf Gddg hMSf Jhajbgs
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdcjejGA hGdWHjYjGJs